Impact of Phylogenetically Diverse Bacterial Endophytes of Bergenia pacumbis on Bergenin Production in the Plant Cell Suspension Cultures - Wawrosch, Christoph; Oberhofer, Martina; Steinbrecher, Stefan; Zotchev, Sergey B. (Planta Medica, 2023)
Plant in vitro cultures are potential sources for secondary metabolites. However, low productivity is often a major drawback for industrial application. Elicitation is an important strategy to improve product formation in vitro. In this context, endophytes are of special interest as biotic elicitors due to their possible interaction with the metabolism of the host plant. A total of 128 bacterial endophytes were isolated from the medicinal plant Bergenia pacumbis and taxonomically classified using 16S rRNA gene sequencing. Five strains belonging to different genera were grown in lysogeny broth and tryptic soy broth medium and cells as well as spent media were used as elicitors in cell suspension cultures of B. pacumbis. Production of the main bioactive compound bergenin was enhanced 3-fold (964 µg/g) after treatment with cells of Moraxella sp. or spent tryptic soy broth medium of Micrococcus sp. These results indicate that elicitation of plant cell suspension cultures with endophytic bacteria is a promising strategy for enhancing the production of desired plant metabolites.
Keywords: Bergenia pacumbis; Saxifragaceae; cell suspension culture; bergenin; endophytes; elicitation